Spectrum of Neonatal Pneumothorax at a Tertiary Care Hospital of Bangladesh : A Retrospective Observational Study. (Bangladesh Critical Care Journal, 2019)
Introduction: Pneumothorax occurs more frequently in the neonatal period than in any other period of life & is associated with increased mortality and morbidity. Several risk factors for pneumothorax, including respiratory pathology, invasive and non-invasive respiratory support & predictors of mortality have been described.Objective: To evaluate the prevalence of pneumothorax, to identify underlying causes & to describe the clinical characteristics, management and outcome of neonates with pneumothorax, as well as to identify predictors of mortality in these neonates.Methods: A retrospective chart review of neonatal records included all neonates hospitalized in the NICU of 'Ad-din Women’s Medical College' Dhaka, between January 2016 & December 2017 with the diagnosis of pneumothorax. The collected data included: demographics & perinatal data, characteristics of pneumothorax, classification, treatment & clinical outcomes. All statistical analyses were performed using the Statistical Package for Social Sciences (SPSS) version 16.Results: Our study included 83 neonates, of whom 48 were male (57.83%) & 60 (72.29%) born by lower uterine caesarean section (LUCS). Median gestational age(GA) was 36 (32-41) weeks & the median birth weight(BW) was 2,558 (1500-3800) grams. The prevalence of neonatal Pneumothorax in our centre was 2.60% & that of Spontaneous Pneumothorax was 1.53%. The analysis of perinatal data showed statistically significant differences in APGAR score at 5th minute (p =